ANALISIS TINGKAT KEPUASAN PENGUNJUNG BIOSKOP XYZ DI PURWOKERTO TERHADAP PELAYANAN DI MASA PPKM (Studi Kasus Salah Satu Bioskop di Purwokerto) - Muhammad Iqbal Tawakal; Famila Dwi Winati; Isnaini Nurisusilawati (JURNAL REKAYASA SISTEM INDUSTRI, 2022)
Cinema is one of the entertainment industries for people in Indonesia. From cinema visitor data in 2019-2021, there is a very significant decrease from 27,646,450 viewers in 2019, 12,059,127 in 2020, and 2,586,386 in 2021. The high number of COVID-19 cases caused the decline, so a level PPKM was issued to stop the spread of this virus. This study aimed to determine the level of satisfaction of consumers or cinema visitors with services during the pandemic and to analyze the level of importance of service performance at the XYZ Purwokerto cinema. Respondents used are 100 respondents, based on calculations using the Lemeshow formula. The methods used will be the CSI (Customer Satisfaction Index) and the IPA (Importance Performance Analysis). The result shows that the satisfaction level of cinema visitors is 74.65%, which means in the satisfied category. Meanwhile, for the results of the analysis using the IPA method, the average level of consumer interest is 4.22, while the performance level is 3.73. Indicators are included in quadrant A or main priority so that there is a need for service improvements that are immediately improved. For example, in the statement of security and cleanliness guarantees during the cinema environment, employees maintain good communication between visitors and employees during the pandemic. The suggested improvement is to sterilize the cinema regularly, spray disinfectant to avoid exposure to viruses, and improve security by adding CCTV in every part of the cinema environment.